Survival now versus survival later: immediate and delayed HIV risk assessment among young Jamaican men who have transactional sex with men - Harris, Orlando O. (Culture, health & sexuality, 2019)
This study explored the experiences of young Jamaican men who have sex with men who engaged in transactional sex as a result of homelessness, family neglect or limited financial resources. It further examined the circumstances that affect their immediate or delayed decisions around sexual risk and increased vulnerability for HIV infection. Barriers experienced when accessing condoms, healthcare, HIV testing and other prevention services are also described. Twenty in-depth interviews and one focus group with 10 participants in various parishes in Jamaica were conducted. Findings from this study reveal how stigma and discrimination in the form of pervasive homophobia-influenced participation in the street economy via transactional sex. Socio-structural factors at family and commity level led to diminished social/economic prospects, which extended into adulthood. Sexual decision making was based on immediate needs for protection, food or shelter; concerns about acquiring HIV were considered only after meeting those immediate needs. Future HIV prevention strategies must take seriously the socio-structural factors that influence HIV risk behaviours among young men who have sex with men in Jamaica.